The role of MPC heterogeneity for fiscal and monetary policy in the Euro Area - Nicolas Albacete; Pirmin Fessler; Atanas Pekanov (Oesterreichische Nationalbank (OeNB), 2024)
Closely following the seminal contribution of Jappelli and Pistaferri (2014) - based on Italian household survey data - we employ data of 22 European countries to assess the role of heterogeneity of the marginal propensity to consume (MPC) for fiscal policy in the Euro area. We document an average MPC of 0.46 in the Euro area and illustrate its heterogeneity across countries, household-characteristics, and major items of the households' balance sheets such as cash-on-hand, liquid, and illiquid wealth. Households with low cash-on-hand have on average higher MPCs. Policy experiments show how the (empirically measured heterogeneity of) MPC affects fiscal policy and makes it more effective in stimulating GDP growth than under the assumption of uniform MPCs. We also illustrate how different MPC patterns lead to similar policies having different effects across the members of the Euro area. Therefore, MPC heterogeneity matters for efficient policy design at the national as well as multinational level. Additionally, we also highlight the role of MPC heterogeneity for monetary policy and deliver a large set of parameters ready to be used in calibrations of Heterogenous Agent New Keynesian and similar economic models.
Keywords: D12; D14; E21; E62; H23; H24; 330; MPC; household survey; fiscal policy; simulations; HANK